2001
DOI: 10.1038/sj.bjp.0704164
|View full text |Cite
|
Sign up to set email alerts
|

Tachykinin NK2 receptors and enhancement of cholinergic transmission in the inflamed rat colon: an in vivo motility study

Abstract: 1 In the gastrointestinal tract, tachykinin NK 2 receptors are localized both on smooth muscle and nerve ®bres. NK 2 receptor antagonists reduce exaggerated intestinal motility in various diarrhoea models but the site of action contributing to this e ect is unknown. In this study we investigated the e ects of atropine (1.4 mmol kg 71 , i.v.), hexamethonium (13.5 mmol kg 71 , i.v.), and nepadutant (0.1 mmol kg 71 , i.v.), a selective tachykinin NK 2 receptor antagonist, on distension (0.5 and 1 ml)-, or irritat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 31 publications
(50 reference statements)
2
21
0
Order By: Relevance
“…In order to rule out the impact of colonic motility per se on the measured balloon pressure variations, the peripherally restricted muscarinic receptor antagonist atropine methyl bromide was used to block the cholinergic excitatory input. A similar approach has been extensively used to inhibit colonic motility in mice, 4,7 rats, 8,20,29,33,37 and humans. 34 The results obtained from the current study show that atropine did not affect repetitive phasic CRD-associated balloon pressure changes, suggesting that colonic motor activity does not contribute significantly to the intraballoon pressure changes registered.…”
Section: Discussionmentioning
confidence: 97%
“…In order to rule out the impact of colonic motility per se on the measured balloon pressure variations, the peripherally restricted muscarinic receptor antagonist atropine methyl bromide was used to block the cholinergic excitatory input. A similar approach has been extensively used to inhibit colonic motility in mice, 4,7 rats, 8,20,29,33,37 and humans. 34 The results obtained from the current study show that atropine did not affect repetitive phasic CRD-associated balloon pressure changes, suggesting that colonic motor activity does not contribute significantly to the intraballoon pressure changes registered.…”
Section: Discussionmentioning
confidence: 97%
“…In human tissue, receptor density seems slightly higher in the colon compared to the bladder (Burcher et al 2000; Warner et al 2003). In vitro contractility studies in several species (human, rat, hamster) demonstrated NK 2 receptor mediated contraction of the bladder (Giuliani et al 1993; Palea et al 1996; Quinn et al 2004; Tramontana et al 1998; Warner et al 2003) and gastrointestinal tract (Carini et al 2001; Lecci et al 2006; Lecci et al 2004; Mule et al 2000). Moreover, the NK 2 receptor mediated bladder contractions in human SCI-induced neurogenic overactive detrusor strips were similar to those from detrusor tissue taken from normal individuals (Sellers et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The long-lasting contraction induced by capsaicin in the mouse rectum may be attributed to the neurokin A reactivity [33]. It has been reported that NK 2 receptor antagonists reduce the fecal output, fecal water content, and/or intestinal hypermotility induced by Salmonella enteritidis endotoxin [34], acetic acid enema [35], Escherichia coli toxin Sta, or Clostridium difficile toxin [36]. Neurokinin A is responsible for the hypermotility associated with diarrheic symptoms.…”
Section: Selectivity Of Inhibitory Effect On Capsaicin-induced Contramentioning
confidence: 98%